Strategies to Advance the Energy Efficiency, Water Efficiency, and Indoor Environmental Quality in New Zealand's Sustainable Building Designs and Practices - Poorisat, Tharaya; Aigwi, Itohan Esther; Doan, Dat Tien; GhaffarianHoseini, Ali (Wiley, 2026)
Sustainable Building Designs and Practices (SBDPs) are increasingly important for reducing environmental impacts, conserving resources, and improving occupant well-being. This study examines New Zealand building professionals' perceptions of the integration and performance of energy efficiency (EE), water efficiency (WE), and Indoor environmental quality (IEQ) in SBDPs. It assesses whether SBDPs are perceived to outperform conventional buildings, identifies key implementation challenges, and explores strategies to strengthen adoption. A quantitative online survey of 102 New Zealand building professionals was conducted to capture perceptions of SBDP performance, barriers and enablers across the three domains. Data were analysed using reliability testing, one-sample t-tests, Kendall's coefficient of concordance, and one-way ANOVA to examine statistical significance, consensus, and stakeholder-group differences. As the study is perception-based, the findings represent perceived rather than empirically measured building performance. The results show that stakeholders perceived SBDPs to outperform conventional buildings across EE, WE and IEQ. EE showed the strongest perceived advantage, while WE was recognised as beneficial but less prominent, suggesting weaker integration within the EE–WE–IEQ nexus. Key barriers included short-term cost priorities, regulatory gaps, and knowledge or coordination deficiencies. Stakeholders favoured passive design, interdisciplinary collaboration, professional training, and incentive-linked regulations, while technology-driven measures were viewed as useful but constrained by cost. The study recommends strengthened building codes, targeted financial incentives, capacity building, and integrated design approaches. By linking stakeholder evidence with practical implementation strategies, this research contributes to SBDP discourse and provides recommendations for policymakers, investors, producers, and practitioners seeking to accelerate sustainable transformation in New Zealand's built environment.
Keywords: Environmental Sciences; energy efficiency; indoor environmental quality; sustainable building designs; sustainable development goals; water efficiency